Environmental Chemistry - Baird C. Colin (New York, W. H. Freeman and Company, 2012)
With up-to-date, balanced, and authoritative coverage of soil, water, and air chemistry, the Fifth Edition offers: Expanded coverage of energy production (especially biofuels), C02 generation and disposal, and innovative ways to combat climate change Increased international coverage to give all students a better perspective on environmental problems and solutions around the world—for example, increased coverage of gaseous and particulate air pollution and COz emissions and air quality standards in both developed and developing countries Updated Green Chemistry cases, including new cases on bio-based toners, recycling carbon dioxide, VOCs in latex paints, bio-based liquid fuels and chemicals, and spinetoram—an improved green pesticide An Activity in most chapters—Web- or library-based mini-projects to be completed either by an individual student or as a group project